Meno’s paradox and the possibility of inquiry - Panahee, Mohammad Raziq. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 2022., 2022)
Plato in his Meno puts forward a challenge against the possibility of inquiry. This challenge has two stages, at one, Meno’s questions challenge the possibility of inquiry in the case of how different kinds of knowledge about one thing are related to each other, at another, Socrates’ argument is supposed to show that either possessing or lacking knowledge about an object entails that one cannot inquire into it. In this study, I present a reading arguing that these two are different challenges; the former is based on strict Socratic requirements on knowing and the latter brings up a puzzle whether inquiry is possible in a general sense. In addition to this, I will analytically discuss and evaluate different possible formulations of Socrates’ argument, some are valid while others are invalid. But before discussing these topics, I will present and evaluate the accounts of Aristotle, Dominic Scott, and Gail Fine in terms of how they understand and solve Meno’s Paradox. I will also investigate whether and how Ilhan Inan’s theory of conceptual curiosity and the specification of the object of one’s curiosity can provide any help to the puzzle of the possibility of inquiry in the Meno.
Keywords: Plato. Meno.; Inquiry (Theory of knowledge); Philosophy, Ancient.